2016
DOI: 10.3989/scimar.04342.01a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gregarious settlement of the stalked barnacle, <em>Pollicipes pollicipes</em>: a laboratory study

Abstract: Summary:Although recruitment patterns of Pollicipes pollicipes (Crustacea: Scalpelliformes) in the wild have been investigated, no studies have yet focused on the factors that affect settlement. In the present paper, settlement of P. pollicipes on conspecifics (gregarious settlement) was investigated in the laboratory as a function of environmental conditions (hydrodynamics, temperature, light and salinity), larval age and batch. This study aimed to understand how these factors modulate settlement in the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…All rights reserved. settlement, we can design more effective, environmentally benign antifouling coatings to which they choose not to attach [11] or, indeed, stimulate settlement where this is desirable such as in the aquaculture of food species [12]. In practice, however, quantitative analysis of barnacle cyprid behaviour is a complex theoretical and practical challenge, and the software and hardware tools available to the field have so far proven inadequate (see Alsaab et al [13] for detailed discussion).…”
Section: Introductionmentioning
confidence: 99%
“…All rights reserved. settlement, we can design more effective, environmentally benign antifouling coatings to which they choose not to attach [11] or, indeed, stimulate settlement where this is desirable such as in the aquaculture of food species [12]. In practice, however, quantitative analysis of barnacle cyprid behaviour is a complex theoretical and practical challenge, and the software and hardware tools available to the field have so far proven inadequate (see Alsaab et al [13] for detailed discussion).…”
Section: Introductionmentioning
confidence: 99%
“…As there are currently no viable protocols for ensuring settlement on artificial substrata of P. pollicipes larvae in the laboratory (see Kugele & Yule ; Franco et al . ), it would also be prudent to build upon the present results and further investigate the implications of larval culture conditions towards competence to settle and ability to complete metamorphosis.…”
Section: Discussionmentioning
confidence: 83%
“…The few published investigations into culture conditions for P. pollicipes (e.g. Goldberg ; Coelho , ; Molares, Tilves & Pascual ; Molares, Tilves, Quintana, Rodríguez & Pascual ; Candeias ; Cribeiro ; Franco, Aldred, Sykes, Cruz & Clare ; Franco, Aldred, Cruz & Clare ) have often identified larval production and settlement as the main bottlenecks to production. Hatchery production is essential to ensure a regulated supply of larvae throughout the year with controlled timing and yield (Franco et al .…”
Section: Introductionmentioning
confidence: 99%
“…Franco et al . (2016) investigated the effects of several factors on P. pollicipes settlement on conspecifics. Their results showed that a few different effects of factors on settlement exist between P. pollicipes and C. mitella .…”
Section: Discussionmentioning
confidence: 99%
“…The sole purpose of the cyprid stage is to locate, explore and attach on a suitable substratum, from where a subsequent complex metamorphosis takes place. Cyprid attachment and metamorphosis is also called ‘cyprid settlement’ (Clare & Matsumura, 2000; Harder et al ., 2001 a ; Franco et al ., 2016). For barnacles, attachment refers to the cementation and fixation of a cyprid onto a surface (Høeg et al ., 2012; Maréchal et al ., 2012; Spremberg et al ., 2012; Dreyer et al ., 2018), whereas metamorphosis denotes the subsequent sequence of morphological, physiological and biochemical events that transform a permanently attached cyprid into a sessile juvenile (Thiyagarajan, 2010; Maréchal et al ., 2012; Maruzzo et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%